Innovation and Inequality : How Does Technical Progress Affect Workers? - Saint-Paul, Gilles (Book collections on Project MUSE., 2008)
Karl Marx predicted a world in which technical innovation would increasingly devalue and impoverish workers, but other economists thought the opposite, that it would lead to increased wages and living standards--and the economists were right. Yet in the last three decades, the market economy has been jeopardized by a worrying phenomenon: a rise in wage inequality that has left a substantial portion of the workforce worse off despite the continuing productivity growth enjoyed by the economy. Innovation and Inequality examines why. Studies have firmly established a link between this worrying tre.